Organic Semiconductor Field-Effect Transistors Based on Organic-2D Heterostructures - Wang, Zi; Huang, Lizhen; Chi, Lifeng (Frontiers in Materials, 2020)
In the past three decades, organic semiconductor field-effect transistors (OFETs) have drawn intense attentions as promising candidates for drive circuits of flat panel display, radio frequency identifications, chemical/bio-sensors and other devices. Generally, the key parameters of OFETs, carrier mobility, threshold voltage and on/off current ratio, are closely related to the degree of order and surface/interface electronic structure of organic semiconductor (OSC) films. The ordering of the films is crucially determined by the molecule-substrate interactions. On inert substrates (such as SiO2) OSC films can hardly reach high order of degree without growth templates, while traditional single crystal surfaces usually force the OSC molecules deviate their favorite assemble manner resulting in an unstable structure. Recently, the rise of two-dimensional materials (2D) provides a possible solution. The in-plane lattice of 2D materials can offer possible epitaxy templates for OSCs while the weak van der Waals (vdWs) interaction between OSC and 2D layers allows more flexibility to realize the epitaxy growth of OSCs with their favored assemble manner. In addition, the various band structures tuned by layer numbers of 2D materials encourage widely modified OSC electronic structures by interface doping between the OSC and 2D layers, which benefits to obtain high-performance OFETs. In this review, we emphasize and discuss the recent advances of OSC-2D hybrid OFETs. The OSC-2D heterostructures not only promote the OFET device performances by film morphology/structure optimization and channel electronic structure modification, but also offer platforms for basic organic solids physics investigations and further functional optoelectronic devices.